2015
DOI: 10.1177/0960327114565492
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic approach for the toxic effects of perfluorooctanoic acid on isolated rat liver and brain mitochondria

Abstract: Background: Perfluorooctanoic acid (PFOA) is one of the most widely used perfluoroalkanes as surfactants, lubricants and processing aids in the production of polymers, which has also been detected in the environment, wildlife and human body. Animal studies indicated that PFOA caused a wide array of toxic effects including liver and brain dysfunction, carcinogenicity and reproductive and developmental toxicity. Based on the established role of mitochondria-mediated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 39 publications
(63 reference statements)
3
31
0
1
Order By: Relevance
“…37 Various concentrations of VEN incubated with 100μL of mitochondrial suspensions equal to 500 μg protein/mL at 37 °C for 30 min pursued by the addition of MTT into the medium and on their incubation time for 30 min at 37°C. The absorbance of produced purple formazan was detected with an ELISA reader (Biotek, ELx800, USA).…”
Section: Mitochondrial Membrane Potential Assaymentioning
confidence: 99%
“…37 Various concentrations of VEN incubated with 100μL of mitochondrial suspensions equal to 500 μg protein/mL at 37 °C for 30 min pursued by the addition of MTT into the medium and on their incubation time for 30 min at 37°C. The absorbance of produced purple formazan was detected with an ELISA reader (Biotek, ELx800, USA).…”
Section: Mitochondrial Membrane Potential Assaymentioning
confidence: 99%
“…While, Verma et al showed observed defects in ADHD strongly is associated with mitochondrial pathology . Also, another study has been reported mitochondrial toxicity could be a plausible mechanism for the toxic effects of PFOA on brain and liver function . PFOA has been reported to cause adenomas of pancreas, testes and liver of animals and delayed development of the mammary gland .…”
Section: Introductionmentioning
confidence: 99%
“…12 Also, another study has been reported mitochondrial toxicity could be a plausible mechanism for the toxic effects of PFOA on brain and liver function. 13 PFOA has been reported to cause adenomas of pancreas, testes and liver of animals and delayed development of the mammary gland. 14 Effects of PFOA on the liver can occur at lesser concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have also shown that exposure to PFOA generates oxidative stress and apoptosis in vitro and in vivo: PFOA exposure significantly inhibited luteal function via oxidative stress and apoptosis in pregnant mice, induced oxidative stress in mouse epididymis and ROS elevation in isolated rat liver and brain mitochondria . The role of ROS within the female reproductive system is complex.…”
Section: Introductionmentioning
confidence: 99%